Study on drug utilization pattern of antihypertensive medication in tertiary care hospital of Telangana, India - Vashishta, K. (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Hypertension is leading cause of deaths in the world. It is the major risk factor for systemic disorders including cardiovascular, renal and brain disorders. A drug utilization review on antihypertensive drugs should be done to determine different classes of antihypertensive medications with respect to diagnosis. Aim was to study drug utilization pattern of antihypertensive medication in a tertiary care hospital, Telangana. Methods: A cross sectional observational study was done in the patients with hypertension for duration of one year i.e. from April 2017 to May 2018 in the department of Pharmacology at Mallareddy Narayana multispecialty hospital, suraram, Telangana. A total 130 Patients who were suffering with acute, chronic hypertension and admitted in general medicine department and undergoing antihypertensive treatment were included. Results: A Total of 130 patients with history of hypertension were included. majority of patients i.e., 46.1% (60/130) were among 51-60 years, followed by 24.6% (32/130) patients among 41-50 years., Male predominance 80/130 61.5%) compared to females 50/130 (38.4%). In the Present study, 105(80.7%) prescriptions had Monotherapy prescription and 25/130 (19.2%) has combination of two. The most frequently prescribed drug as monotherapy was Calcium Channel Blockers (CCBs) about 52.3%, Beta blockers constitute about 14.2%, and diuretics about 19%, 9.5% Angiotension Receptor Blockers (ARBs) and alpha-Adrenergic Blocker (AABs), 4.7% ACE inhibitors. Conclusions: Calcium channel blockers are the highest among the drugs that are used as monotherapy. In combination therapy, diuretic with angiotensin receptor blocker and calcium channel blocker with beta blocker are the frequently prescribed drugs.